TINJAUAN YURIDIS PENGAJUAN PRAPERADILAN OLEH PIHAK KETIGA ATAS PENGHENTIAN PENYIDIKAN ATAU PENUNTUTAN DALAM PERKARA KORUPSI - Gendis Wahyuningrum; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Pretrial is a new institution introduced by the Criminal Procedure Code. As for the function that is owned by the pretrial institute is to conduct surveillance against the existence of a horizontal action lapses and abuses of authority committed by police agencies as investigators and prosecution agencies as the public prosecutor. The supervision is done is part of the implementation of the integrated criminal justice system. In the process, emerging issues at pretrial. One of them is the vagueness of interpretation in CRIMINAL PROCEDURE CODE concerning who is the third party concerned in article 80 of the CODE of CRIMINAL PROCEDURE. So in this research aims to know the parties can be said to be the third party concerned and weaknesses faced by third parties in filing pretrial upon termination of investigation or prosecution in the case of corruption. The research method used authors are research methods with normative approach to legislation.As pretrial legal effort new mechanism is very beneficial to the community in order to avoid the occurrence of forced efforts conducted by Investigators in the process of arrest, detention, investigation and prosecution. Issuance of letter of the Ordinance termination of a lawsuit (SKP3) for the accused in corruption matters always invites controversy, debate, and give rise to the perception that tends to be negative towards the performance of law enforcement agencies, in particular the Prosecutor's Office. The barriers commonly encountered in practice pretrial usually, the first weak legal factors itself, which lies in the weakness of the existing provisions in the legislation, the second factor is the lack of law enforcement in dealing with the problem of corruption, which is the third factor of law culture, officials here tend to be serious in dealing with the eradication of corruption, even the law enforcement agencies are often the perpetrators of corruption itself, and the latter political factors, the politicians had been allegedly often conspire with the parties that is problematic in corruption. Based on the above, it is expected that the law enforcement officers who act as investigators and prosecutors should be more thorough and professional in carrying out the task either investigation, investigation, and prosecution. And also institutions that make the rules should be more careful in making and formulating a rule. because of the vagueness of the rules will only be a weak point that will be easily exploited to escape from the law.Keywords: Pretrial - third parties - investigation - prosecution